Using Wool Keratin as a Basic Resist Material to Fabricate Precise Protein Patterns. Issue 28 (12th May 2019) - Zhu, Shuihong; Zeng, Wenbin; Meng, Zhaohui; Luo, Wenhao; Ma, Liyun; Li, Yanran; Lin, Changxu; Huang, Qiaoling; Lin, Youhui; Liu, Xiang Yang
Abstract: The ability to pattern natural polymers at different scales is extremely important for many research areas, such as cell culture, regenerative medicine, bioelectronics, tissue engineering, degradable implants, and photonics. For the first time, the use of wool keratin (WK) as a structural biomaterial for fabricating precise protein microarchitectures is presented. Through straightforward biochemical processes, modified WK proteins become intrinsically photoreactive without significant changes in protein structure or function. Under light irradiation, intermolecular chemical crosslinking between WK molecules can be successfully initiated by using commercially available photoinitiators. As a result, high‐performance WK patterning on the micrometer scale (µm) can be achieved through a combination of water‐based photolithography techniques. By simply mixing with nanoparticles, enzymes, and other dopants, various "functional WK resists" can be generated. In addition, without the addition of any cell‐adhesive ligands, these patterned protein microstructures are demonstrated as bio‐friendly cellular substrates for the spatial guidance of cells on their surface. Furthermore, periodic microfabricated WK structures in complex patterns that display typical iridescent behavior can be designed and formed over macroscale areas (cm). Abstract : "Photoresist‐like" wool keratin is used for fabricating well‐defined, high‐quality, and high‐resolution protein patterns over large areas via direct‐write photolithography without the need of toxic chemicals, high temperature, or harsh processing conditions. Moreover, the design and development of such large‐scale sustainable protein microstructures have widespread applications, such as the spatial guidance of cells and soft optical systems.